Modelling Pulse Magnetic Welding Processes - Uhlmann, E.; Ziefle, A. (Institut für Umformtechnik - Technische Universität Dortmund, 2010)
In recent years pulse magnetic welding technology gained an ever increasing attention. The process was known for over 40 years, yet the poor knowledge of process parameters as well as the difficulties concerning the calculability of the process due to lack of adequate software, performance and appropriate material models hindered the application of the technology. In the past, some simulations treating the process of explosive welding were conducted. There, the assumption was made to define a friction condition to the boundary regions which was reasonable due to similar conditions in the collision region during the process. However, at pulse magnetic welding processes, the contact forces are highly transient and have big gradients over the geometry. In this paper a new empirical approach is presented, which gives the possibility of modelling the welding process by parameter-controlled bonding at the welding interface. The pulse magnetic forming process was simulated by loose coupling of electromagnetic and mechanical FEM software with the commercial code ANSYS. As geometry the joining of a duct with an internally positioned conical bolt was chosen. The material used for both duct and bolt was EN AW 6063. First of all the influences of heat generation were analyzed. Therefore, the additional thermal simulation was coupled with the electromagnetic and the mechanical simulation. The heat generation caused by the plastic deformation was considered. As the resulting temperatures were below the melting temperature of the material, further simulations were carried out without thermal simulation. In order to calibrate the welding model, a set of relevant parameters were defined. It included the cumulative plastic work, the plastic deformation in collision direction, the normal and the tangential components of the collision velocity and the collision angle between the two parts. By comparing the simulation with experiments carried out at the same specific process parameters, it was possible to reduce the set of parameters to the normal collision velocity and plastic deformation. Based on their distribution, the parameter control of the bonding condition could be adjusted. Further experiments gave a high accordance to the simulations carried out with the parameters found for this model.
An Empirical Approach
Keywords: finite element method (FEM); parameter controlled bonding; pulse magnetic welding; 620; 670